Offshore wind energy: A review of the current status, challenges and future development in Spain. (October 2016) - Colmenar-Santos, Antonio; Perera-Perez, Javier; Borge-Diez, David; dePalacio-Rodríguez, Carlos
Abstract: Offshore wind energy generation has experienced an important growth in the last five years, reaching currently an installed capacity of almost 8000 MW. The most important references in this type of technology are Denmark, Holland, Sweden, Germany and United Kingdom. In Spain, previsions for technology, have been set at around 750 MW of installed power during the period 2011–2020. However, Spanish coastal features, social opposition to installations near the coast and lack of a stable regulatory environment guaranteeing the investments are factors which are restraining the development of this technology. This paper presents a brief review of the state of the art of offshore wind technology and it describes the most frequently used types of turbines, transmission systems and support structures in Europe. It also presents the current situation and the expected growth of offshore wind power facilities, introducing the characteristics of the operational – and under construction – windfarms. Finally, it analyses particular problems and solutions for its development in Spain which can be extrapolated to countries with similar circumstances.